Development of Core Qualities of Childcare Teachers in the Context of Childcare Integration - Deng, Fengyan (Journal of Educational Research and Policies, 2025)
Kindergartens are seizing the opportunity to transform into integrated childcare as the population shows negative growth and the country promotes the development of universal childcare. In order to adapt to the kindergarten’s transformation of child care integration, kindergarten teachers have also switched to child care positions and become child care teachers. During the period of work adaptation, childcare teachers face dilemmas in terms of philosophy, knowledge, competence and affectivity.